Analisis kesadaran hukum terhadap pelanggaran penggunaan sepeda motor oleh anak di bawah umur di SMP Negeri 1 Kerinci - Putri, Septin Habillah; Salam, M.; Ichsan, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was presented to determine the level of legal awareness regarding violations of motorbike use by minors at SMP Negeri 1 Kerinci. This research was conducted at SMP Negeri 1 Kerinci located : Jln. Raya Pugu Semurup, Desa Pugu Raya, Kecematan Air Hangat Barat, Kabupaten Kerinci. The samples that will be used as subjects for this research include: Students of SMP Negeri 1 Kerinci, parents of students of SMP Negeri 1 Kerinci who use motorbikes to school, Student Representatives of SMP Negeri 1 Kerinci, and the Kerinci Traffic Police (Polantas). The approach used is a qualitative descriptive approach. The resulting data will be a description in the form of words and does not emphasize data in the form of numbers. The data obtained and collected in this research was then analyzed so that it could be explained further. The research results showed that students have low legal awareness, where this can be seen from students' low knowledge and understanding of law, there are still many children who do not know the legal bases that regulate traffic and road transportation. Meanwhile, legal attitudes and behavior are categorized as quite high, where SMP Negeri 1 Kerinci has established rules that must be obeyed by students of SMP Negeri 1 Kerinci, and Traffic Police have carried out their duties in accordance with procedures that have been regulated or determined by law.